Interference of anesthetics in blood alcohol analysis by HS-GC-FID: A case report. (August 2016) - Monteiro, C.; Proença, P.; Tavares, C.; Castañera, A.; Corte Real, F.
Highlights: We emphasize the importance of using two columns of different polarities in ethanol analysis by HS-GC-FID. Among other parameters, the study of selectivity is very important in the validation of a method by HS-GC-FID. Volatile anesthetics may be possible interferents in the analysis by HS-GC-FID. Abstract: One of the techniques most widely used in ethanol analysis in forensic laboratories is undoubtedly the headspace gas chromatography with flame-ionization detection (HS-GC-FID) since the determination of this substance is carried out directly, without the need for additional purification procedures, which leads to increased productivity. This is a very important factor due to the high number of alcohol analysis requested to these laboratories. The presence of other volatile substances can cause a problem given the fact that they can be interferents in ethanol analysis by HS-GC-FID, which can have legal consequences related with driving under the influence of alcohol. The authors report a case of a routine analysis by HS-GC-FID for the determination of ethanol of a driver who has suffered an accident in which the use of two chromatographic columns with different polarities was essential to obtain an unequivocally identification of this substance in presence of an interfering volatile anesthetic administered in the hospital. The method was validated according to international recommendations before being introduced into routine laboratory in terms of selectivity, limits of detection (LOD), limits of quantification (LOQ), linearity, repeatability, intermediate precision, accuracy, robustness and carryover.